La recepció del teatre espanyol a Catalunya. Un cas d’estudi: El último mono (1926) de Carlos Arniches i la seva adaptació catalana (L’adroguer del carrer Nou, 1929) - Orazi, Veronica (Studia Romanica Posnaniensia, 2021)
Study of the reception of Carlos Arniches’ play El último mono in Catalonia, through the analysis of its Catalan translation. Starting from the identification of the characteristic features of the author’s theatre, as presented in the work under examination, the strategy of transposition into the resulting hypertext will be defined, according to the different types of treatment (preservation, adaptation, replacement, elimination, etc.) of the key elements, both in terms of content as well as of language and style.